Isten veled hazánk! - László, Gábor (Hungary, 2012)
In 1947 following the Soviet occupation of Hungary, thousands of Germans living in Hungarian border towns were expelled from the country and relocated to different parts of the continent. These people considered themselves to be fully Hungarian, and were forced to leave their homes, families, and posessions. Hungarian and German witnesses recount their memories of this time period.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films